2011
DOI: 10.1007/s00432-011-1068-z
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of specified microRNAs in peripheral blood as biomarkers for metastatic non-small-cell lung cancer by stem-loop RT-PCR

Abstract: PurposeTo investigate the levels for some specified microRNAs in human’s peripheral blood so as to determine whether they can serve as biomarkers for metastatic non-small-cell lung cancer.MethodsUse a quantitative stem-loop RT-PCR method to examine the serum levels for certain microRNAs including has-miR-125a-5p, has-miR-126, has-miR-183, has-miR-200, has-miR-221, and has-miR-222 from the patients with Stage IV, Stage I/II non-small-cell lung cancer and the controls.ResultsThere was statistical difference in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…For instance, miR-183 is highly represented in serum relative to urine. Serum levels of miR-183 have been described in case/control studies where significantly lower levels of miR-183 are observed in stage IV non-small-cell lung carcinoma versus controls-making it a potential biomarker target for lung cancer [20]. In addition, a clinically aggressive medulloblastoma has been linked to the pleiotropic effects of the miR-183 cluster [21].…”
Section: Results and Discussion (A) Exosome Isolation And Rna Recoverymentioning
confidence: 99%
“…For instance, miR-183 is highly represented in serum relative to urine. Serum levels of miR-183 have been described in case/control studies where significantly lower levels of miR-183 are observed in stage IV non-small-cell lung carcinoma versus controls-making it a potential biomarker target for lung cancer [20]. In addition, a clinically aggressive medulloblastoma has been linked to the pleiotropic effects of the miR-183 cluster [21].…”
Section: Results and Discussion (A) Exosome Isolation And Rna Recoverymentioning
confidence: 99%
“…With regard to the discriminatory capacity of miR-30d-5p, the favorable distinguishing ability revealed by both the SROC curves for GEO meta-analysis and the integrated meta-analysis hinted at the potential use of miR-30d-5p for screening of NSCLC. Considering the non-invasive nature of the circulating miRNA-based test, circulating miRNAs might conceivably surpass tissue mRNAs as the most attractive screening tools for NSCLC [43,44]. Therefore, a SROC curve was specially created for plasma miR-30d-5p levels.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent reports demonstrated that circulating miRNAs levels were significantly increased in cancer plasma or serum samples compared to control groups (31)(32)(33)(34)(35), including NSCLC (36,37). But some miRNAs expressions are lower in cancer groups than in control groups.…”
Section: Discussionmentioning
confidence: 99%